Are there Obstacles after the Administrative Court Absolute Competence Extension of Indonesia? - Kadek Agus Sudiarawan; I Gusti Ngurah Wairocana; Bagus Hermanto (Varia Justicia, 2020)
The enactment of the Law Number 30 Year 2014 regarding Government Administration with the expansion of Administrative Court competence stimulate confusion and obstacles in norms and theoretical also practical obstacles for the justice enforcers especially Administrative Court Judges. On the other hand, this law is contrary and potentially conflict with Government Administration Law. To resolve this legal problem, Indonesia Supreme Court issuing several Supreme Court Regulation and Circular Letter of Supreme Court for each expansion of Administrative Court competence otherwise the confusion and obstacle in theoretical and practical spheres still conducted the problem for the justice enforcers. This study has aims to analyze and discuss concerning confusion and obstacles faced by enforcers especially Administrative Court Judges and the attitude or solution towards those obstacles. This study is using normative and empirical method with qualitative types as a descriptive analysis article.